Faktor-faktor yang Memengaruhi Kejadian Stunting Pada Bayi Usia 2 Tahun - Sinaga, Desriati; Sinabariba, Merlina; Siallagan, Ermawaty A. (Jurnal Maternitas Kebidanan, 2024)
Stunting is a condition where infants experience growth failure due to malnutrition that has been experienced for a long period of time, exposed to repeated infections and not supported by adequate stimulation. The 0-24 month period is a golden period that determines the quality of life and is very sensitive because the consequences caused to babies in that period will be permanent and irreparable. The purpose of this study was to analyze the factors that influence the incidence of stunting  for 2 years old babies. The research design used in this study was descriptive analytic. The population in this study were 2-year-old babies in the work area of the Katarina Simanjuntak Clinic and the sampling technique in this study was a purposive technique, namely a sampling technique based on certain criteria predetermined by the researcher with a total of 98 people. Secondary data were collected using the MCH book and primary data were collected using microtoise instruments and questionnaires. The results of data analysis showed that infant variables associated with the incidence of stunting were infant birth weight and history of MP breastfeeding. Statistically significant factors were birth weight with a p-value of 0.001 and history of MP breastfeeding with a p-value of 0.003. This study can be used as a reference material for health workers in efforts to prevent stunting by optimizing complementary feeding and stimulation, especially in infants with low birth weight..